Architectural Design as an Attraction for UMKM (Micro, Small, and Medium Enterprises) Culinary Delights in Ruteng City - Eleonora Vilgia Putri Beyan; Maria Kalista Hadia Sabu; Anastasia Ruli; Viktorianus F. S. Ganjur (Widya Teknik, 2026)
The challenges in developing culinary UMKM (Micro, Small, and Medium Enterprises) in Ruteng City cannot be separated from the quality of business space design, which significantly influences consumer attraction and purchasing decisions. As a small city with strong cultural potential and abundant local resources, Ruteng faces difficulties in enhancing the competitiveness of its culinary businesses amid the dominance of the informal sector and limitations in spatial planning. Appropriate architectural design not only functions as a physical setting for economic activities but also serves as a visual and experiential strategy capable of stimulating consumer interest, strengthening local identity, and creating a distinctive business image. This study aims to examine the role of architectural design in enhancing the attractiveness of culinary UMKM in Ruteng City by identifying design elements that influence consumer behavior and business appeal. The research employs a descriptive qualitative approach using a benchmarking method, analyzing the design characteristics of successful culinary business units in Labuan Bajo as references and adapting them to the local context of Ruteng. Data collection techniques include field observations, visual documentation, and interviews with UMKM owners and consumers to understand spatial preferences, consumer expectations, and operational requirements. The study is expected to generate architectural design recommendations that can enhance the attractiveness and competitiveness of culinary UMKM in Ruteng City through the integration of Manggarai cultural values, local characteristics, and the functional needs of business owners. In addition to providing practical contributions to the development of a culinary-based creative economy, this research also contributes to the growing discourse on the relationship between architectural design, place identity, and consumer behavior within the context of small cities in Indonesia.